Astrophysical studies in Tajikistan: from traditional approach overmodeling to empirical properties - Kokhirova, G. I.
New approach developed in the Institute of Astrophysics, Academy of Sciences of the Republic of Tajikistan, aimed to determination of the relationships between Solar System minor bodies is considered. The method consists of modeling of objects motion in the past or in the future, calculation of theoretical parameters, identification of the theoretically predicted properties with the observed ones. Usage of the method allowed to recognize extinct cometary nuclei among the near-Earth asteroids and to establish the parent bodies of some known asteroid-meteoroid complexes.
Keywords: Astrophysics